Luces de la ciudad - Chaplin, Charlie, 1889-1977.; Cherrill, Virginia, 1908-1996.; Garcia, Allan, 1887-1938.; Lee, Florence, 1888-1962.; Mann, Hank, 1887-1971.; Myers, Harry, 1886-1938.; Pollock, Gordon, m. 1956.; Totheroh, Roland H., 1890-1967. (MK2 Editions : Distributed by Warner Home Video, 2003)
A tramp wins the love of a blind flower girl and attempts to obtain money from a millionaire to help her regain her sight.